Implementation Of Counseling On Legs Exercises In The Elderly With Diabetes Mellitus - Erma Mariam; Ria Muji Rahayu; Yossinta Salindri (PITIMAS: Journal of Community Engagement in Health, 2022)
Abstract Introduction : Diabetes mellitus is a chronic disease characterized by the inability of the body to metabolize carbohydrates, fats, and proteins early so that hyperglycemia occurs).Materials/methods : Implementation of examination, treatment, and foot exercises for people with diabetes mellitus was attended by 50 residents. Prior to education, a pre-test was carried out in the form of examination, treatment and exercise for DM's feet, residents carried out regular blood sugar checks, blood pressure checks and measurements of weight and height.Results : Elderly participants have less knowledge about diabetes mellitus and foot exercises are still lacking. Participants said that they had never received counseling about foot exercises.Conclusions : Examination, treatment and exercise for diabetic feet are highly recommended for people with diabetes mellitus to prevent complications of diabetic neuropathy. Keywords: Leg Exercise, Elderly, Diabetes mellitus Abstrak Pendahuluan : Diabetes melitus merupakan penyakit kronis yang ditandai dengan adanya ketidakmampuan tubuh untuk melakukan metabolisme karbohidrat, lemak, dan protein awal sehingga terjadi hiperglikemia), Metode : Pelaksanaan kegiatan pemeriksaan, perawatan, dan senam kaki bagi penderita diabetes mellitus dihadiri 50 warga. sebelum dilakukan edukasi dilaksanakan pre test berupa pemeriksaan, perawatan dan senam kaki DM, warga melakukan pemeriksaan gula darah sewaktu, pemeriksaan tekanan darah dan pengukuran berat badan dan tinggi badan. Hasil : Peserta lansia mempunyai pengetahuan yang kurang tentang diabetes mellitus dan senam kaki masih kurang. Peserta mengatakan bahwa mereka belum pernah mendapatkan penyuluhan tentang senam kaki. Kesimpulan : Pemeriksaan, perawatan dan senam kaki diabetes sangat dianjurkan bagi penderita diabetes mellitus untuk mencegah komplikasi neuropati diabetik.